Comparative life cycle assessment of LED lighting products. (October 2018) - Casamayor, JL; Su, D; Ren, Z
The use of LED lighting products is growing rapidly. However, there are no in-depth, updated studies that show how to assess and compare these products for eco-design purposes. This research aims to inform eco-design by assessing and comparing the environmental impact of a new LED eco-lighting product with an existing LED lighting product. A cradle to grave life cycle assessment is conducted. The system boundaries include all product life cycle stages, except the maintenance of the luminaires and the manufacturing of the packaging. A novel functional unit is defined for the assessment, which is more suitable for LED lighting products. Six scenarios are considered, including three probable useful lives of the luminaires (1000, 15, 000 and 40, 000 hours) and two end of life options (domestic bin and recycling centre). The life cycle assessment results reveal that the new eco-lighting product has about 60% less environmental impact than the existing lighting product in all scenarios. The life cycle stages with the biggest impacts are, in decreasing order: (1) use, (2) manufacturing, (3) end of life and (4) transport. Recommendations for the eco-design of LED lighting products are proposed, and the challenges in applying life cycle assessment for eco-design are discussed.